Nutritional benefits of pancreas‐sparing total duodenectomy for severe duodenal polyposis in patients with familial adenomatous polyposis - Ibuki Fujinuma; Toshiro Ogura; Ayano Takahashi; Satoshi Nomura; Kei Kitamura; Amane Takahashi; Takehiro Shiraishi; Yoshiko Mori; Toru Ishiguro; Takatoshi Matsuyama; Youichi Kumagai; Hideyuki Ishida (Annals of Gastroenterological Surgery)
Abstract Aim Severe duodenal polyposis associated with familial adenomatous polyposis considerably increases the risk of duodenal cancer. Pancreas‐sparing total duodenectomy is an alternative surgical approach for managing severe duodenal polyposis. This study evaluated the postoperative nutritional outcomes following pancreas‐sparing total duodenectomy in patients with severe duodenal polyposis associated with familial adenomatous polyposis. Methods This retrospective analysis compared 28 patients who underwent pancreas‐sparing total duodenectomy for Spigelman stage IV duodenal polyposis with 29 patients who underwent pancreatoduodenectomy for low‐malignancy duodenal neoplasms. Patient demographics, postoperative complications, and nutritional parameters were analyzed at 3, 6, 9, and 12 months postoperatively. Results Compared with patients in the pancreatoduodenectomy group, those in the pancreas‐sparing total duodenectomy group were younger and had a higher incidence of previous abdominal surgeries (p < 0.01). Postoperatively, the pancreas‐sparing total duodenectomy group showed significantly better preservation of total protein, albumin, and total cholesterol levels, body mass index, body weight, and psoas major muscle area compared to the pancreatoduodenectomy group (p < 0.05). Additionally, glucose tolerance was better maintained in the pancreas‐sparing total duodenectomy group than in the pancreatoduodenectomy group (p < 0.01), with no patients requiring the initiation of insulin therapy or experiencing the exacerbation of diabetes. Conclusions Pancreas‐sparing total duodenectomy effectively preserves the postoperative nutritional status in patients with duodenal polyposis associated with familial adenomatous polyposis. This surgical option maintains postoperative nutritional integrity and improves long‐term outcomes.